Particulate adjuvants for therapeutic uses - BOUSAFSAF , Salsabil; BOUCHENINE , Narimene; KEBAILI , Hakima Supervisor (Sétif 1 University Ferhat Abbas . Faculty of Natural and Life Sciences, 2025)
This manuscript explores the crucial role of adjuvants—substances used to enhance the effectiveness of pharmaceuticals such as vaccines, antibiotics, antibodies, and chemotherapy. Adjuvants are classified into two main types: delivery systems (e.g., aluminum salts, emulsions, microparticles) and immunostimulants (e.g., TLR and NOD receptor agonists), which help activate and direct the immune response. The study highlights the adjuvants use in overcoming bacterial resistance (e.g., clavulanate, avibactam), improving the efficacy of therapeutic vaccines for complex diseases like cancer and Alzheimer’s (e.g., MF59, AS04), stimulating antibody production in animals (e.g., FCA), and enhancing chemotherapy after surgery to reduce relapse risks. Despite their effectiveness, adjuvants still face challenges related to cost and side effects, underlining the need for safer, more targeted, and accessible alternatives in the future of medical treatments.
Keywords: Pharmaceutical adjuvants